A pathological scapula in a mosasaur from the upper Maastrichtian of Antarctica: Evidence of infectious arthritis and spondyloarthropathy - Talevi, Marianella; Rothschild, Bruce; Fernández, Marta Susana; Reguero, Marcelo Alfredo; Mitidieri, Matías (Cretaceous Research)
We describe infectious arthritis and spondyloarthropathy in a juvenile mosasaur recovered from the upper Maastrichtian of Antarctica, representing the first report of a skeletal pathology of a mosasaur from the southern hemisphere. Macroscopic examination of the scapula revealed a remodelled, deeply excavated and expanded gleno-humeral joint with adjacent linear disruption. X-ray examination revealed a deep excavation expanding the glenoid fossa, with disorganized subchondral bone and a focal spherical defect. The individual did not continue to grow for a long time after the appearance of the lesion. Although not directly related to the mosasaur death, this condition may have contributed to the demise of the animal by reducing its effectiveness at obtaining food or increasing susceptibility to fatal disease, additional injury, or even predation. Fil: Talevi, Marianella. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina. Universidad Nacional de Río Negro. Sede Alto Valle. Instituto de Investigaciones en Paleobiología y Geología; Argentina Fil: Rothschild, Bruce. The Carnegie Museum; Estados Unidos. Indiana University; Estados Unidos Fil: Fernández, Marta Susana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Reguero, Marcelo Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Mitidieri, Matías. Universidad Nacional de Río Negro. Sede Alto ...